SISTEM INFORMASI GEOGRAFIS DALAM PENETAPAN LOKASI PENJUALAN PROPERTI (STUDI KASUS CV RUMAH JOGJA PROPERTI) - Kuncoro Widodo; Rr Yuliana Rachmawati K; Suraya - (Jurusan Informatika INSTITUT SAINS & TEKNOLOGI AKPRIND YOGYAKARTA, 2018)
In this modern world, humans need communication and information technology which is practical, effective, flexible and versatile. An example is information about property location services. Properti is primary needs for humans. Limited of information received by the prospective buyer makes difficulty in finding information about the property. The existence of the data make sure that the creation of applications using android platform right thing to do. In this research admin will be provided web-based applications to provide information about property location services, while users will be provided with mobile applications using the android platform to receive location service property information.This research used property data from CV Rumah Jogja Properti, regional data in Indonesia, location service data, and map data provided by Google Map. The tools needed for web admin in this research is programming language which consists of Java, HTML, CSS, Javascript, and PHP, text editor used for template android application is Eclipse Mars, database created using MySQL. besides template, database and Web programming language is also required support tools such as laptops, USB data cable, Smartphone, android SDK manager, and Apache as a web server for system design, as well as computer peripherals.The result of this research is location service application consisting of application for web based admin and mobile application for user. Admin can manage all data like the one on web. While the user can only search property information as well as perform routing from the user location to the location of the property. This application also provides a explore menu that can be used to find support locations in accordance with existing categories.